Metabolismo de nitrogênio, parâmetros digestivos e exigência de proteína para mantença de búfalas em crescimento - Machado, Erica (2014)
The objective was to evaluate the nitrogen metabolism, digestibility of nutrients and ruminal parameters in the diet of buffaloes containing increasing levels of crude protein, and to estimate the requirement of protein for maintenance this category animal. Four crossbred growing buffaloes were used, weighing 355 ± 3.5 kg of body weight, cannulated in the rumen and distributed in a 4×4 Latin square design, with four animals and four levels of crude protein (70, 90, 110 and 130 g.kg-1) and four periods. The diets were consisted in corn silage and concentrate, and was formulated to meet the proposed levels of CP. The intake was ad libitum, allowing 50 - 100 g.kg-1 of refusals. The levels of CP influenced the dry matter intake and others nutrients, however did not influence nutrienst digestibility and ruminal kinetic. The nitrogen balance increased linearly with the increasing levels of CP, however, when expressed in relation to nitrogen intake, with an average of 485.50 g.kg-1, this effect is not confirmed. The blood metabolites (urea and total proteins) were influenced by diets and protein requirements for maintenance of the animals in these conditions, obtained by the intercept of the regression of nitrogen balance and nitrogen intake was 4.63 g PB.kg W-0.75.